Analysis of The Influence of Accounting Information System and Leadership Style on Performance of Employees in National Poultry Farming Company - Windi Novia Ratri Wardhani; Asep Suherman; Dian Ariani; Santi Nururly; Herni Utami Rahmawati (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
The era of globalization, which increases information technology, has increased competition in the business world. Companies in this era are increasingly complex and competitive. Every business must be prepared to deal with technical advancements, all consumer wants, and fierce rivalry from other businesses. Companies need a solid plan if they wish to survive the competition. The purpose of this study is to examine how leadership style and the caliber of accounting information systems affect employee performance. This study makes use of first-hand information gathered via accountant survey data. Nonprobability sampling was the method of selection that was employed in this study. This study adopts a quantitative methodology and makes use of IBM SPSS and non-parametric statistical analysis techniques. The test results demonstrate that leadership style and the caliber of the accounting information system are key determinants of employee success.